Volitional type of facial palsy associated with pontine ischaemia. Issue 6 (June 1995) - Töpper, R; Kosinski, C; Mull, M
Abstract : A dissociation between voluntary and emotional facial innervation is described in a patient with a pure motor stroke due to a unilateral ischaemic pontine infarction. Voluntary facial innervation of the contralateral orbicularis oris muscle was affected whereas emotionally induced innervation of the same muscle was spared. This report provides evidence that fibres conveying voluntary and emotional commands are still separated in the pons. Whereas corticobulbar tracts carry the information for voluntary facial innervation, efferents from the amygdala and the lateral hypothalamus are candidates for the somatomotor aspects of emotions.